2007
DOI: 10.4102/sajbm.v38i2.579
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into responsible tourism practices in the South African hotel industry

Abstract: This paper sheds light on the reasons for the limited uptake of responsible tourism initiative memberships by hotels in South Africa, despite South Africa being regarded as a leader in the field of responsible tourism policy, with the drafting of responsible tourism guidelines by the South African Department of Environmental Affairs and Tourism (DEAT). The International Centre for Responsible Tourism’s conference (hosted in South Africa) preceding the World Summit on Sustainable Development in 2002 resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…The respondents, who are also members of the industry associations, indicated that EMPs are not an important factor to help create competitive advantage. This outcome is similar to a study carried out for South African hotels (Van der Merwe and Wocke, ), and Chan and Wong () revealed that none of their studies found that competitors play a role in influencing hotels to adopt EMPs.…”
Section: Discussionsupporting
confidence: 88%
“…The respondents, who are also members of the industry associations, indicated that EMPs are not an important factor to help create competitive advantage. This outcome is similar to a study carried out for South African hotels (Van der Merwe and Wocke, ), and Chan and Wong () revealed that none of their studies found that competitors play a role in influencing hotels to adopt EMPs.…”
Section: Discussionsupporting
confidence: 88%
“…First, corporate donations tend to align with societal expectations, and hence are viewed as a tool by which societal legitimacy could be achieved (Dal Maso et al ., ). Second, corporate donations are often used by tourism firms in building a good image with national governments, non‐governmental organizations (NGOs) and investors (Van der Merwe and Wocke, ). Third, philanthropic initiatives may be undertaken by some firms for purely altruistic reasons in the form of ‘giving back to society’ (McLachlan and Binns, ).…”
Section: A Comparative Analysis Of Csr In the Tourism (Hospitality) Imentioning
confidence: 97%
“…The increased uptake of environmental initiatives in the South African tourism industry in relation to their counterparts in the region is for two fundamental reasons. First, some firms are becoming environmentally orientated to align with the needs of stakeholders such as government policy and the needs of environmentally aware western consumers, and also to achieve green certifications (Van der Merwe and Wocke, ; Frey and George, ). Secondly, the increased adoption of environmental initiatives reflects the commitment of owners and managers to environmental issues.…”
Section: A Comparative Analysis Of Csr In the Tourism (Hospitality) Imentioning
confidence: 97%
“…As Porter & Kramer point out CSR, corporate social investment and ethical management practices have emerged as strong trends in many industries but evidence of actual change remains relatively limited in tourism (2006). Only 2% of tourism businesses globally are participating in responsible tourism or CSR initiatives such as the Global Compact, and South African studies into the hotel and tour operator sub-sectors show low levels of transformation (Spenceley, 2007;Van der Merwe & Wö cke, 2007;Wijk & Persoon, 2006). Since the Brundtland Report of 1987 (UN, 1987) proposed that intergenerational equality would not be achieved unless the impacts of economic activity on the environment were managed, both debate and research into sustainable tourism practices and philosophies have increased.…”
Section: Introductionmentioning
confidence: 98%